Marina Tsvietáieva and María Zambrano didn’t meet at Paris - Santiago Bolaños, Marifé (Tropelías: Review of Literary Theory and Comparative Literature, 2020)
In the first months of 1939, Marina Tsvietáieva and María Zambrano were in Paris awaiting for some documents. The poet, those allowing to return to Rusia, after decades of absence. The philosopher, those allowed her to leave for America. Apparently, the poet was finishing her exile while the philosopher was starting hers. Both of them, coming from those geographical extremes that would end up tearing out themselves from the common idea of ​​Europe. And both of them shared a personal, social and symbolic common burden mirrored in their works: a world of shameless violence, where women’s creativity and thought received the deserved and rightful echo. This article focusses on the search for a new common space, imagining what their conversation could have been in case Marina Tsvietáieva and María Zambrano had met.